Cryoprotectant‐free vitrification of spermatozoa: Fish as a model of human. (8th October 2018) - Isachenko, Vladimir; Sanchez, Raul; Rahimi, Gohar; Mallmann, Peter; Isachenko, Evgenia; Merzenich, Markus
Abstract: Post‐thawing motility of spermatozoon, which is directly correlated with the integrity of mitochondrion, is the main parameter for evaluation of respective cryopreservation treatments. In this review, we describe our model of mitochondrial apparatus of spermatozoa and behaviour of this apparatus during cryopreservation. This model shows why a priori the mitochondrial apparatus of the human spermatozoon is expected to be more cryo‐stable than the mitochondrial apparatus of the fish spermatozoon. Negative changes of mitochondrial membrane potential are a good indicator of the functional normality of mammalian and fish spermatozoa. It is concluded that the cryostability of mitochondrial membranes of fish spermatozoa is lower than that of human spermatozoa, and protocols for effective cryopreservation of fish spermatozoa can be extrapolated to human spermatozoa. It is also provided a biological explanation for why cryoprotectant‐free vitrification for human ejaculates is better than conventional freezing and vitrification with cryoprotectants. This review also includes a description of the various technologies of vitrification of human and fish spermatozoa. For cryobiological investigations, we propose to evaluate the fish spermatozoon as a suitable representative model of the human spermatozoon.